1997
DOI: 10.1080/00288233.1997.9513242
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Compudose® and Rumensin®, alone or in combination, on the growth, and carcass and meat quality of steers finished on pasture

Abstract: Rumensin® (monensin sodium) and Compudose® (oestradiol-176) can both promote liveweight gain of pasture-fed cattle. Limited information exists about their effects on carcass and meat quality characteristics or their combined effects on beef cattle performance. This study examined the effects of Rumensin (R) and Compudose (C), alone and in combination, on the growth, carcass characteristics, and meat quality of steers finished at pasture. Seventy-two yearling steers (290 ± 4 kg) received either no treatment, R,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
3
1
Order By: Relevance
“…This was also found in the BCS that tend to be greater in E2 steers than the two other groups, although it did not attain statistical significance. In contrast, a study in the use of HGP (Compudose® and Rumensin® in finishing steers) showed that the implant treatment significantly increased the BCS along with the increase of LWG (Burnham et al 1997). The difference between the current study and the study of Burnham et al (1997) was probably due to the small number of measurements conducted in the current experiment prevented the detection of significance.…”
Section: Endocrine and Blood Metabolitescontrasting
confidence: 84%
“…This was also found in the BCS that tend to be greater in E2 steers than the two other groups, although it did not attain statistical significance. In contrast, a study in the use of HGP (Compudose® and Rumensin® in finishing steers) showed that the implant treatment significantly increased the BCS along with the increase of LWG (Burnham et al 1997). The difference between the current study and the study of Burnham et al (1997) was probably due to the small number of measurements conducted in the current experiment prevented the detection of significance.…”
Section: Endocrine and Blood Metabolitescontrasting
confidence: 84%
“…Cattle (13,410 animals; 247 ± 41 kg BW) were British, Continental or B. indicus breeds. References: Monensin: Bagley et al, 1981;Bagley and Feazel, 1989;Burnham et al, 1997;Cochran et al, 1990;Darden and Wolfrom, 1988;Davenport et al, 1989;Horn et al, 1981;Horn et al, 1988;Keith et al, 1995;Merrill and Stobbs, 1986;Muller et al, 1986;Oliver, 1975;Parrott et al, 1990;Parrott et al, 1986;Potter et al, 1976;Potter et al, 1986;Rossi et al, 1997;Rouquette et al, 1980;Smith et al, 1995;Spears et al, 1989;Utley et al, 1976;Wagner et al, 1984. Lasalocid: Andersen andHorn, 1987;Delcurto et al, 1989;Keith et al, 1995;Paterson et al, 1983;Rode, 1987;Rode et al, 1994;Spears and Harvey, 1984;Thonney et al, 1981;Valdes et al, 1988;Worrell et al, 1990.…”
Section: Methodsmentioning
confidence: 97%
“…Since monensin X implant interaction (P N 0.8), the main effects are presented. This analysis included 16 comparisons (n = 4, Burnham et al, 1997;Cochran et al, 1990;Parrott et al, 1990;Wagner et al, 1984). Repetitions/ comparison (mean ± S.D.)…”
Section: Administration Of Agp To Cattle Under Grazing Conditions: Camentioning
confidence: 99%
“…Larsen and Grunert, 2003). Although the use of ionophores has been shown to have a limited effect on meat quality (Boucqué et al, 1982;Burnham et al, 1997), the use of hormonal implants may increase the incidence of dark cutters and beef toughness (Scanga et al, 1998;Roeber et al, 2000;Barham et al, 2003). However, implants can have variable impacts on intramuscular fatty acid profile depending on composition and duration of implant used (Kennett and Siebert, 1987;Duckett et al, 1999).…”
Section: Introductionmentioning
confidence: 99%